Improving The Ability To Identify Fold Symmetry Of Plane Figures In Mathematics Subjects Using The Inquiry Method - Simanjuntak, Haholongan; Sihaloho, Endah Triasih Br (LPPM Universitas PGRI Sumatera Barat, 2023)
The methods used by each teacher are diverse, one of which is the discovery/inquiry method for the lessons or materials studied to increase and improve student learning achievement. Classroom Action Research (CAR) which is divided into two cycles uses the Classroom Action Research (CAR) design which is divided into two cycles. Each cycle consists of 4 (four) stages, namely: (1) Improvement Plan, (2) Implementation of Improvement, (3) Data Collection, (4) Reflection. The research was conducted at SDK Nasional Plus PENABUR Bandar Lampung, with a total of 25 third grade students consisting of 13 male students and 12 female students. The results of the study before the cycle showed that students still had not mastered the material, especially in determining the symmetry of plane figures, in the process they obtained a completion value of 60% while in cycle I the achievement of completion results was 64%, in cycle II it reached 88% completion, this proves that after using the inquiry method, students were active in teaching and learning activities. From the results of the study, it is clear that by using it, it can improve students' learning achievement in learning Mathematics for National Plus SDK PENABUR Bandar Lampung students, especially in identifying the Fold Symmetry of Plane Shapes